A field experiment on dust emission by wind erosion in the Taklimakan Desert - Yang, Xinghua; Strake, Miriam (Acta meteorologica Sinica, 2012)
Dust emission by wind erosion in surface is a serious problem in many arid regions around the world, and it is harmful to the ecological environment, human health, and social economy. To monitor the characteristics of saltation activity and to calculate the threshold wind velocity and sediment discharge under field conditions have significance on the research of dust emission by wind erosion. Therefore, a field experiment was conducted over the flat sand in the hinterland of the Taklimakan Desert. One sampling system was installed on the flat sand surface at Tazhong, consisting of a meteorological tower with a height of 2 m, a piezoelectric saltation sensor (Sensit), and a Big Spring Number Eight (BSNE) sampler station. Occurrence of saltation activity was recorded every second using the Sensit. Each BSNE station consisted of five BSNE samplers with the lowest sampler at 0.05 m and the highest sampler at 1.0 m above the soil surface. Sediment was collected from the samplers every 24 h. It is found that saltation activity was detected for only 21.5% of the hours measured, and the longest period of saltation activity occurring continuously was not longer than 5 min under the field conditions. The threshold wind velocity was variable, its minimum value was 4.9 m s−1, the maximum value was 9.2 m s−1, and the average value was 7.0 m s−1. The threshold wind velocity presented a positive linear increase during the measurement period. The observation site had a sediment discharge of 82.1 kg m−1 over a period of 24 h. Based on hourly saltation counts, hourly sediment discharge was estimated. Overall, there was no obvious linear or other functional relationship between the hourly sediment discharge and wind velocity. The results show that the changes of sediment discharge do not quite depend on wind velocity.
Gesehen am 03.04.2018